Superconductivity at 35 K by self doping in RbGd2Fe4As4O2. (7th February 2017) - Wang, Zhi-Cheng; He, Chao-Yang; Wu, Si-Qi; Tang, Zhang-Tu; Liu, Yi; Ablimit, Abduweli; Tao, Qian; Feng, Chun-Mu; Xu, Zhu-An; Cao, Guang-Han
Abstract: We report synthesis, crystal structure and physical properties of a novel quinary compound RbGd2 Fe4 As4 O2 . The new iron oxyarsenide is isostructural to the fluo-arsenide KCa2 Fe4 As4 F2, both of which contain separate double Fe2 As2 layers that are self hole-doped in the stoichiometric composition. Bulk superconductivity at T c = 35 K is demonstrated by the measurements of electrical resistivity, dc magnetic susceptibility and heat capacity. An exceptionally high value of the initial slope of the upper critical field ( μ 0 d H c 2 /d T | T c = 16.5 T K −1 ) is measured for the polycrystalline sample.